Catalyst-assisted selective vinylation and methylallylation of a quaternary carbon center using tert-butyl acetate - Mohanta, Nirmala; Samal, Pragnya Paramita; Pandey, Akanksha M.; Mondal, Shankhajit; Krishnamurty, Sailaja; Gnanaprakasam, Boopathy (Journal of Organic Chemistry, 2023)
The In-(OTf)(3)-catalyzed & alpha;-vinylationof varioushydroxy-functionalized quaternary carbon centers using in situ generatedisobutylene from tert-butyl acetate is presentedas a novel synthetic methodology. Moreover, tert-butylacetate is a nonflammable feed stock and is a readily available sourcefor the in situ production of vinyl substituents, as demonstratedby the vinylation reaction with quaternary hydroxy/methoxy compounds.Moreover, an excellent selectivity for methylallylation over vinylationwas obtained with Ni-(OTf)(2) as a catalyst. In the case ofperoxyoxindole, methylallyl-functionalized 1,4-benzoxazin-3-one derivativeswere formed through the sequential rearrangement of peroxyoxindolefollowed by the nucleophilic attack by isobutylene. The detailed mechanismfor this reaction and rationalization for the selectivity are providedusing kinetics and density functional theory studies.

FeCl2-catalyzed rearrangement of aryl peroxyoxindole into 1,3-benzooxazin-4-One - Mohanta, Nirmala; Samal, PragnyaParamita; Krishnamurty, Sailaja; Gnanaprakasam, Boopathy (Advanced Synthesis & Catalysis, 2023)
We report an FeCl2-catalyzed radical rearrangement of aryl peroxyoxindoles into 1,3-benzooxazin-2-ones to obtain a variety of aryl substituted 1,3-benzooxazin-4-ones in moderate to good yields. Mechanistically, this skeletal rearrangement of peroxyoxindoles proceeded via radical pathway and was well supported with a series of experimental findings and DFT studies.
Keywords: 1; 3-Benzooxazin-4-one; FeCl2; Peroxyoxindole; rearrangement; Ring expansion